ENSIKLOPEDIA mengenal sains : IPA dan Teknologi / Penerjemah, Reynaldo Krissancha Azarya dan Febe Fenyta S.; Penyunting, Dewi Susiloningtyas, F. Yulianto, dan M. Surianto - REYNALDO Krissancha Azarya; FEBE Fenyta S; DEWI Susiloningtyas; YULIANTO, F.; SURIANTO, M. (Aku Bisa, 2012)
128 hlm. : ilus. ; 29,5 cm.